Butyrate can support PAOs but not GAOs in tropical climates - Wang, Li (2022)
Glycogen accumulating organisms (GAOs) are thought to compete with polyphosphate accumulating organisms (PAOs) for the often-limiting carbon sources available in wastewater, deteriorating enhanced biological phosphorus removal (EBPR) performance at high temperatures. Fermentation liquids are often used to provide an additional carbon source supply in EBPR processes, where butyrate is known to be an important volatile fatty acid (VFA) produced in sludge fermentation. Nevertheless, the impact of butyrate on the PAO-GAO competition is not well understood especially at high temperature. The results of this study demonstrate that butyrate, as a supplemental or sole carbon source, could be promising for EBPR in tropical climates. When the carbon source was gradually changed from acetate to butyrate, a substantial PAO population was found under both conditions, despite a substantial shift in the abundance of Candidatus Accumulibacter phosphatis (decreased from 37.4% to 13.9%) to Rhodocyclaceae (increased from 2.0% to 14.5%), where both organisms likely played an important role in P-removal. Thus, a relatively stable P removal performance was realized throughout the whole operation period. Nevertheless, butyrate had a negative impact on GAOs. The biomass concentration and microbial diversity continually decreased in the GAO reactor, and Candidatus Competibacter phosphatis reduced from 27.3% to 6.2%, where the dominant population was replaced by Zoogloea. With the addition of butyrate as carbon source, the total amount of synthesized PHAs reduced in both PAO and GAO cultures and the composition of PHA was greatly changed. The presence of a novel PHA fraction (PHH) may disturb the microbial activity in the aerobic phase, where the GAO culture was more severely affected. Glycogen cycling also seemed to be limited in both reactors. This could reduce the GAO metabolism in both cultures and favor PAOs and P removal. Furthermore, the biomass growth rate of the PAO culture was higher than that of GAO when fed with butyrate, which also provides PAO a competitive advantage. All the above results indicate that butyrate could not be well metabolized by GAOs, but could provide PAOs a competitive advantage. Thus, mixed VFAs (i.e. acetate, propionate and butyrate) are likely to favor PAOs over GAOs in EBPR processes operated in warm climates, where the impact of substantial butyrate fractions represents an advantage towards successful process operation.